The Relationship of Hyperemesis Gravidarum with Anemia in First Trimester Pregnant Women at the Midwife Clinic Yani Delitua in 2022 - Rini Febrianti (Pena Cendekia Insani, 2022)
Hyperemesis gravidarum is a complaint of nausea and vomiting that is categorized as severe if pregnant women always vomit every time they drink or eat. As a result, the body is very weak, the face is pale, and the frequency of urination decreases drastically, daily activities are disrupted and the general condition decreases. The purpose of this study was to determine Hyperemesis Gravidarum with Anemia in First Trimester Pregnant Women at the Midwifery Clinic Yani Delitua in 2022. This study is an analytical survey using an analytical approach. This research was cross sectional. This study was conducted at the Midwifery Clinic Yani Delitua in 2022 starting from January-May 2022. The population in this study were all pregnant women with TM I in April-May 2022 as many as 31 people. The sampling technique in this study was carried out by using the total population technique. The research sample was 31 people. The results were analyzed using univariate and bivariate analysis with the chi-square test. %).Anemia da ri 31 respondents pregnant women with hyperemesis as many as 16 respondents (51.6%) and pregnant women with emesis as many as 15 respondents (15%)